INTERACTIVE METHODS OF TEACHING RUSSIAN GRAMMAR - Osmanova Maryam Soibxonovna (Journals Park Publishing, 2024)
This article explores interactive strategies for teaching Russian grammar, emphasizing gamification, multimedia resources, and collaborative learning. It highlights how these methods enhance student engagement, promote deeper comprehension, and foster language proficiency. Through innovative approaches, educators can create dynamic learning environments that empower students to master Russian grammar with enthusiasm and confidence.
Keywords: Russian grammar, collaborative learning, immersive experiences, gamification, empower students, enhance proficiency.